2018
DOI: 10.1038/s41419-017-0258-2
|View full text |Cite
|
Sign up to set email alerts
|

miR-143-3p targeting of ITGA6 suppresses tumour growth and angiogenesis by downregulating PLGF expression via the PI3K/AKT pathway in gallbladder carcinoma

Abstract: Gallbladder cancer (GBC) is the most common malignant tumour of the biliary track system. Angiogenesis plays a pivotal role in the development and progression of malignant tumours. miR-143-3p acts as a tumour suppressor in various cancers. Their role in GBC is however less well defined. Here we show that the expression levels of miR-143-3p were decreased in human GBC tissues compared with the non-tumour adjacent tissue (NAT) counterparts and were closely associated with overall survival. We discovered that miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(66 citation statements)
references
References 35 publications
(42 reference statements)
4
59
0
Order By: Relevance
“…LKB1 inhibits GBC cell progression via the JAK/STAT3 cascade. Several signaling pathways, including JAK/STAT3, PI3K/Akt, MEK/ERK and EMT have been reported to play a role in the proliferation of GBC cells (27)(28)(29)(30)(31)(32). In this study, our data demonstrated that PI3K/Akt and MEK/ERK pathways, and EMT were not affected by LKB1 overexpression, while the phosphorylation of the STAT3 molecule was evidently activated in both the SGC-996 and GBC-SD LKB1 control cells (Fig.…”
Section: Downregulation Of Lkb1 In Gbc Cscssupporting
confidence: 52%
“…LKB1 inhibits GBC cell progression via the JAK/STAT3 cascade. Several signaling pathways, including JAK/STAT3, PI3K/Akt, MEK/ERK and EMT have been reported to play a role in the proliferation of GBC cells (27)(28)(29)(30)(31)(32). In this study, our data demonstrated that PI3K/Akt and MEK/ERK pathways, and EMT were not affected by LKB1 overexpression, while the phosphorylation of the STAT3 molecule was evidently activated in both the SGC-996 and GBC-SD LKB1 control cells (Fig.…”
Section: Downregulation Of Lkb1 In Gbc Cscssupporting
confidence: 52%
“…Our results appear to support the idea that miR-143-3p acts as a tumor suppressor due to its effects on cell metastasis and invasion via targeting ITGA6. Jin et al 34 also indicated that miR-143-3p could suppress tumor growth and angiogenesis by targeting ITGA6 and PLGF through the PI3K/AKT pathway in gallbladder carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…According to Zhang and colleagues, miR-33a was down-regulated in human GBC tissues, which functioned as a tumor suppressor in GBC by targeting Twist [14]. Jin et al found that miR-143-3p was down-regulated in GBC tumor tissues and was an inhibitor of GBC progression [17]. Hence, miRNAs may be used as therapeutic markers for GBC [18].…”
Section: Discussionmentioning
confidence: 99%